RAMA'S LEADERSHIP BETWEEN MORAL DILEMMA AND PREJUDICE - I Made Arsa Wiguna; I Nengah Alit Nuriawan (Samā Jiva Jnānam (International Journal of Social Studies), 2025)
This paper examines the leadership of Shri Rama in the Ramayana epic through the perspective of morality and social prejudice. The author uses the method of textual study and the approach of literary hermeneutics, to reveal the various moral dilemmas faced by Rama and the prejudices that arise against his decisions as a leader. Although viewed as an ideal leader (Rajaṛṣi), Rama's decisions in dealing with conflicts between personal, professional, and social obligations invite controversy and ethical debate. Some of the main events analyzed include his refusal to return to Ayodhya, the exile of pregnant Sita, and the banishment of Lakshmana. This paper highlights the importance of integrity, consistency to dharma, and justice in leadership, while showing that being a true leader often means making difficult decisions that are not always popular, but are based on deep ethical and moral considerations.